Ancient runoff harvesting agriculture in the arid Beer Sheva Valley, Israel: An interdisciplinary study. (August 2020) - Haiman, Mordechai; Argaman, Eli; Stavi, Ilan
Between 2004 and 2008, a wealth of ancient agriculture-related finds was uncovered during a survey throughout the loess plains of the Beer Sheva Valley region, in the arid northern Negev, Israel. The survey was conducted under the framework of an archeological study, aimed at assessing the similarities and dissimilarities of the valley's ancient agricultural systems to those of the Negev Highlands to the south and of the Judean Lowlands and Southern Hebron Mountains to the north. Data collection from selected sites included detailed mapping of settlements and their hinterlands. Ancient runoff farming systems, comprised of relatively uniform stone terraces transecting the wadis (ephemeral stream channels), and other agriculture-related structures, such as tuleilat el anab (spatially patterned stone mounds erected on hillslopes), were revealed throughout the region. Other archeological finds included a variety of structures, including livestock pens, square watchtowers, rock-cut water cisterns, and others. This study indicates that like the agricultural systems in the neighboring southern and northern regions, the systematic terracing of wadis across the Beer Sheva Valley region was affiliated with the monastic settlement system, which was centrally managed by the church in the service of the Byzantine Empire. The significance of this settlement system stems from its highly capable central organization, aiming to achieve geo-political control of space. Despite peaking in the mid-6th century CE, this system persisted throughout the Early Islamic period, until the mid-8th century CE. Results of this study contradict the conclusions of previous studies, which negated the viability of ancient runoff farming across the loess plains of the Beer Sheva Valley region. Insights of this research highlight the need for interdisciplinary studies when assessing the interactions between human populations and the natural environment in ancient times.